Perception management: A Content Analysis of the Greek Reality Show ‘Survivor’ - Papakonstantinou, Katerina G.; Zarkada, Anna K.; Panigyrakis, George G. (My University, 2018)
The purpose of this paper is to explore the relationship between the application of various perception management techniques and the success of the 2017 Greek version of the reality TV show ‘Survivor’, which repeatedly achieved the unprecedented viewership of 80%. Utilising a theory-driven content analysis of audio-visual data (32 episodes and a total of 86,5 hours) it is demonstrated that all perception management techniques identified in the literature were employed in the show and the frequency and intensity of their use was directly correlated with viewership.
Keywords: Perception management; content analysis; reality television show; social television; Survivor